Analisis Faktor-Faktor Mempengaruhi Produktivitas Karyawan di Purnama 2 Laundry - Sri Gina Annisa; Syahrial Shaddiq (PT. Saha Kreasi Indonesia, 2025)
One important measure of efficient human resource management in service-based firms, especially in micro, small, and medium-sized enterprises (MSMEs), is employee performance productivity. As a small-scale laundry service company, Purnama.2 Laundry must maintain maximum employee efficiency to guarantee client happiness, service quality, and business competitiveness. Analyzing the variables affecting Purnama 2 Laundry employees' performance and productivity is the goal of this study. A survey approach was used in a quantitative study design. Structured questionnaires were used to gather data from all Purnama 2 Laundry staff, and multiple linear regression analysis was used to examine the results. Employee performance productivity is the dependent variable, whereas work motivation, work environment, work discipline, and remuneration are the independent variables that are investigated. The findings show that every independent variable has a statistically significant and favorable impact on worker productivity and performance. According to these results, enhancing employee enthusiasm, fostering a positive work atmosphere, regularly enforcing work discipline, and offering equitable and proportionate compensation are all important ways that human resource management can boost productivity. When developing sustainable methods to improve staff performance and service quality, MSME managers can benefit from the empirical evidence and practical insights provided by this study.